2018
DOI: 10.1051/0004-6361/201731751
|View full text |Cite
|
Sign up to set email alerts
|

Chandra and ALMA observations of the nuclear activity in two strongly lensed star-forming galaxies

Abstract: Aims. According to coevolutionary scenarios, nuclear activity and star formation play relevant roles in the early stages of galaxy formation. We aim at identifying them in high redshift galaxies by exploiting high-resolution and sensitivity X-ray and millimetre-wavelength data to confirm the presence or absence of star formation and nuclear activity and their relative role in shaping their SEDs and contributing to their energy budget. Methods. In the current paper we present the data, model and analysis in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
7
35
0
Order By: Relevance
“…Our expectations are consistent with the measured sizes of z ≈ 2 star-forming galaxies (see Barro et al 2016aBarro et al , 2017Hodge et al 2016;Genzel et al 2017;Tadaki et al 2017b;Massardi et al 2018;van Dokkum et al 2015;Talia et al 2018). Specifically, sizes inferred from near-IR/optical data (light blue symbols) are seen to be located in between R Q and R rot , while sizes inferred from mid/far-IR data (dark blue symbols) lie around and within R rot .…”
Section: Growth By Dry Mergingsupporting
confidence: 90%
See 2 more Smart Citations
“…Our expectations are consistent with the measured sizes of z ≈ 2 star-forming galaxies (see Barro et al 2016aBarro et al , 2017Hodge et al 2016;Genzel et al 2017;Tadaki et al 2017b;Massardi et al 2018;van Dokkum et al 2015;Talia et al 2018). Specifically, sizes inferred from near-IR/optical data (light blue symbols) are seen to be located in between R Q and R rot , while sizes inferred from mid/far-IR data (dark blue symbols) lie around and within R rot .…”
Section: Growth By Dry Mergingsupporting
confidence: 90%
“…High-resolution, multi-band observations (e.g., Negrello et al 2014;Massardi et al 2018) of strongly lensed dusty star-forming galaxies have also highlighted a clear spatial segregation between the UV and far-IR emissions, with the latter being substantially more concentrated. Note that the extremely large dispersion in the data points for star-forming galaxies is in part spuriously due to this difference between near-IR and far-IR sizes; however, even when considering data with homogenous selection, the dispersion remains substantial, in agreement with our expectation regarding the scatter on R Q and R rot .…”
Section: Growth By Dry Mergingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the differences in the calculated star formation rates could indicate the presence of an AGN, which boosts the IR luminosity and artificially inflates the star formation rate derived from that quantity, while leaving the SFR calculated from the radio free-free emission, which is disentangled from the nonthermal AGN contribution, unaffected. Recently, X-Ray observations conducted with the Chandra X-Ray Observatory (Massardi et al 2018), and dense-gas tracers observed with ALMA (Oteo et al 2017), have both been detected to be co-spatial with the peak of the dust continuum, suggesting the presence of an AGN within SDP.11, making this scenario plausible.…”
Section: Star Formation Ratementioning
confidence: 98%
“…However, most of these studies are limited in spatial resolution and only investigate their globally averaged properties. Spatially resolved observations with angular resolution approaching the characteristic scales of star-forming regions are still rare (e.g., Swinbank et al 2015;Cañameras et al 2017;Dye et al 2018;Sharda et al 2018;Massardi et al 2018). In order to understand the detailed physical properties of high-redshift SMGs, especially their complex intrinsic structures, it is crucial to acquire high angular resolution images.…”
Section: Introductionmentioning
confidence: 99%